Recent Advancements of Monotherapy, Combination, and Sequential Treatment of EGFR/ALK-TKIs and ICIs in Non–Small Cell Lung Cancer - Liao, Dehua; Yu, Lun; Shangguan, Dangang; Zhang, Yongchang; Xiao, Bowen; Liu, Ni; Yang, Nong (Frontiers in Pharmacology, 2022)
Lung cancer is the leading cause of cancer-related deaths with high morbidity and mortality. Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 85% of all cases of lung cancer. Fortunately, the development of molecular oncology provides promising and effective therapeutic strategy for lung cancers, including specific gene mutations/translocations and immune checkpoints, with epidermal growth factors receptor (EGFR) common mutations first and anaplastic lymphoma kinase (ALK) translocations later as the targeted therapy and immune checkpoint inhibitors (ICIs) as the immunotherapy. This review summarizes the recent common therapies of TKIs and ICIs in NSCLC, and focuses on the clinical effect of combination or sequential treatment so as to provide effective advice for the treatment of NSCLC.